New species of Eibesfeldtphora Disney (Diptera: Phoridae) and a new key to the genus - Uribe, Soraya; Brown, Brian V.; Bragança, Marcos A.l.; Queiroz, Jarbas M.; Nogueira, Carlos A. (Zootaxa, 2014)
Two new species of parasitoids, Eibesfeldtphora trifurcata and Eibesfeldtphora inornata, are described. Both species were collected in Brazil. A new key is provided and illustrated for the twenty one known species.